Organic Chemistry with a Biological Emphasis Volume I - Soderberg, Tim; Open Textbook Library (Open Textbook Library, 2016)
The traditional approach to teaching Organic Chemistry, taken by most of the textbooks that are currently available, is to focus primarily on the reactions of laboratory synthesis, with much less discussion - in the central chapters, at least - of biological molecules and reactions. This is despite the fact that, in many classrooms, a majority of students are majoring in Biology or Health Sciences rather than in Chemistry, and are presumably taking the course in order to learn about the chemistry that takes place in living things.In an effort to address this disconnect, I have developed a textbook for a two-semester, sophomore-level course in Organic Chemistry in which biological chemistry takes center stage. For the most part, the text covers the core concepts of organic structure, structure determination, and reactivity in the standard order. What is different is the context: biological chemistry is fully integrated into the explanation of central principles, and as much as possible the in-chapter and end-of-chapter problems are taken from the biochemical literature. Many laboratory synthesis reactions are also covered, generally in parallel with their biochemical counterparts - but it is intentionally the biological chemistry that comes first.
Chapter 1: Introduction to organic structure and bonding, part I -- Section 1: Drawing organic structures -- Section 2: Functional groups and organic nomenclature -- Section 3: Structures of some important classes of biological molecules -- Chapter 2: Introduction to organic structure and bonding, part II -- Section 1: Covalent bonding in organic molecules -- Section 2: Molecular orbital theory -- Section 3: Resonance -- Section 4: Non-covalent interactions -- Section 5: Physical properties of organic compounds -- Chapter 3: Conformation and Stereochemistry -- Section 1: Conformations of open-chain organic molecules -- Section 2: Conformations of cyclic organic molecules -- Section 3: Chirality and stereoisomers -- Section 4: Labeling chiral centers -- Section 5: Optical activity -- Section 6: Compounds with multiple chiral centers -- Section 7: Meso compounds -- Section 8: Fischer and Haworth projections -- Section 9: Stereochemistry of alkenes -- Section 10: Stereochemistry in biology and medicine -- Section 11: Prochirality -- Chapter 4: Structure determination part I - Infrared spectroscopy, UV-visible spectroscopy, and mass spectrometry -- Section 1: Mass Spectrometry -- Section 2: Introduction to molecular spectroscopy -- Section 3: Infrared spectroscopy -- Section 4: Ultraviolet and visible spectroscopy -- Chapter 5: Structure determination part II - Nuclear magnetic resonancespectroscopy -- Section 1: The origin of the NMR signal -- Section 2: Chemical equivalence -- Section 3: The 1H-NMR experiment -- Section 4: The basis for differences in chemical shift -- Section 5: Spin-spin coupling -- Section 6: 13C-NMR spectroscopy -- Section 7: Solving unknown structures -- Section 8: Complex coupling in 1H-NMR spectra -- Section 9: Other applications of NMR -- Chapter 6: Overview of organic reactivity -- Section 1: A first look at some organic reaction mechanisms -- Section 2: A quick review of thermodynamics and kinetics -- Section 3: Catalysis -- Section 4: Comparing biological reactions to laboratory reactions -- Chapter 7: Acid-base reactions -- Section 1: Acid-base reactions -- Section 2: Comparing the acidity and basicity of organic functional groups- the acidityconstant -- Section 3: Structural effects on acidity and basicity -- Section 4: Acid-base properties of phenols -- Section 5: Acid-base properties of nitrogen-containing functional groups -- Section 6: Carbon acids -- Section 7: Polyprotic acids -- Section 8: Effects of enzyme microenvironment on acidity and basicity -- Chapter 8: Nucleophilic substitution reactions -- Section 1: Two mechanistic models for nucleophilic substitution -- Section 2: Nucleophiles -- Section 3: Electrophiles -- Section 4: Leaving groups -- Section 5: SN1 reactions with allylic electrophiles -- Section 6: SN1 or SN2? Predicting the mechanism -- Section 7: Biological nucleophilic substitution reactions -- Section 8: Nucleophilic substitution in the lab
In English.
Description based on online resource
Keywords: Science -- Textbooks; Chemistry -- Textbooks